2017
DOI: 10.1016/j.celrep.2017.10.070
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-cancer Analysis of the Expression and Clinical Relevance of Small Nucleolar RNAs in Human Cancer

Abstract: Increasing evidence has demonstrated that small nucleolar RNAs (snoRNAs) play important roles in tumorigenesis. We systematically investigated the expression landscape and clinical relevance of snoRNAs in >10,000 samples across 31 cancer types from The Cancer Genome Atlas. We observed overall elevated expression of snoRNAs and their ribonucleoproteins in multiple cancer types. We showed complex regulation of snoRNA expression by their host genes, copy number variation, and DNA methylation. Unsupervised cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
218
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(224 citation statements)
references
References 53 publications
4
218
2
Order By: Relevance
“…In our study, we found the six-snoRNA signature expressed stably in serum, suggesting serum snoRNAs may serve as novel non-invasive biomarkers for ccRCC. 19 In this study, we found high expression of risky factors SNORD12B and SNORD93 Interestingly, according to the results of ROC and 3-D PCA, we found the six-snoRNA signature performance in tissue was better than that in serum.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In our study, we found the six-snoRNA signature expressed stably in serum, suggesting serum snoRNAs may serve as novel non-invasive biomarkers for ccRCC. 19 In this study, we found high expression of risky factors SNORD12B and SNORD93 Interestingly, according to the results of ROC and 3-D PCA, we found the six-snoRNA signature performance in tissue was better than that in serum.…”
Section: Discussionsupporting
confidence: 53%
“…19,32,33 Therefore, we evaluated relevance of CNV and these snoRNA expressions. is a key regulator of gene expression, and some snoRNAs were significantly associated with their CNVs in various cancers.…”
Section: The Snorna Methylation and Wnt Pathway Potentially Functiomentioning
confidence: 99%
See 2 more Smart Citations
“…SnoRNAs could be regulated by their host genes, copy number variation, and DNA methylation . Some scientists pointed out that the host genes may affect the expression of snoRNAs by cotranscription; however, other scholars reported that the functions of some SNHG members were independent of their snoRNAs . Moreover, recent studies have shown that some snoRNAs are also related to cancer tumorigenesis .…”
Section: Small Nucleolar Host Genes and Snornasmentioning
confidence: 99%